Lifestyle of Kazakhstan’s middle class in contemporary conditions - Burkhanova, D. K. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2015)
Over the past few years, the political, economic and social situation in Kazakhstan has changed a lot. Kazakhstan has managed to create an enabling environment for private sector development and attracting foreign direct investment, through decisive reforms in the economic and financial sec tors, which led to the development of energy and oil & gas sectors. Within twenty years of independence the country has risen to a very high level of economic and today is an example of a successful transition among the CIS.Nowadays in the conditions of the stable development of Kazakhstan’s economy the problem of formation and development of the middle class is very important and urgent. The government relies on predominance of the middle class in society, which is regarded as a «comfort class», which pro vides political and social stability in the developed countries of the world. As a result of this perspective, the creating an enabling environment for further successful development of the middle class is one of the main priorities of social and economic policy in Kazakhstan. This article presents some results of a sociological research conducted in April 2013 with the support of the Cen tre of Sociological Research and Social Engineering in Almaty, Kazakhstan in order to determine the values and economic strategies of Kazakhstan middle class. Sampling is a multistage quota, reflecting a representative totality of the demographic structure of the city. Along with the quantitative survey, 20 expert interviews were conducted. The authors developed an approach to allocate the middle class of Kazakhstan; also in this article authors provided the evaluation and analysis of the current lifestyle of Kazakhstan middle class. In general, summing up approaches presented in this study, it can be noted that they rely on the broader definition of middle class. In this case, to the middle class are included those whose needs appear above basic human needs such as food and clothing, and thus has necessary resources and the intention to raise living standard thanks to the skillful use of their knowledge and skills.